Comparative Analysis of Investment Behavior and Strategies Between Male and Female Investors at the Universitas Muhammadiyah Makassar - Nurul Auliyah Bakri; Nasrullah Nasrullah; Nurlina Nurlina (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the comparison of investment behavior and strategies between male and female investors at Universitas Muhammadiyah Makassar. This phenomenon is important to understand because gender differences can affect the way individuals make investment decisions, both in terms of risk tolerance, asset preferences, and portfolio management strategies. Using a qualitative approach, data were collected through in-depth interviews with students who are actively investing. The data was analyzed using thematic methods to identify patterns of investment behavior and strategies based on gender. The results show that male investors tend to take higher risks and use speculative strategies, while female investors are more cautious, with a focus on long-term investment and risk management. This research provides insights into the influence of gender in investment decision-making, which can be used to develop more inclusive financial education.